Implementation mechanisms of self-efficacy in Arabic language subject at secondary religious school - Mohd Sani, Ismail; Aman Daima, Md. Zain; Mohd Hasrul, Shuhari; Mohd Safri, Ali (2019)
In today’s world of education system there are various challenges and intricacies with numerous demands and needs that are to be solved. In the context of Arabic language learning, it is generally found that low ability and comprehension of Arabic language learning has a great impact on the progress and performance of students in the education system nationally. Ergo, there is a demand to address this Arab language learning issue from persevering to offer efficient methods and means of learning. This study was conducted to explore the mechanism of self-efficacy application which became a vital requirement in Arabic language learning conducted in Secondary Religious School. The foundation and guidelines for analyzing the study are adopting the Self- Efficacy theory which is the suitable theory to obtain information on ways to improve the student’s self-efficacy and comprehension followed by the mastery of students towards Arabic language. The study was completely implemented adopting qualitative approaches through interviews and both direct and indirect observations conducted in the field of study, using research in libraries and online surveys. Hence, perpetual studies on Arabic language education need to be implemented by providing efficient dimensions of teaching and learning to enable them to provide excellent human capital in academia not only in Arabic learning but also in other subjects.